Birth rates after radioactive iodine treatment for differentiated thyroid cancer - Anderson, Chelsea (Int J Cancer, 2017)
Treatment with radioactive iodine (RAI) for differentiated thyroid cancer has been associated with alterations in gonadal function in women, including changes in menstrual function and an earlier age at menopause. Our objective was to evaluate associations between RAI and post-diagnosis live birth rates among thyroid cancer survivors diagnosed at ages 15–39 years. We identified women diagnosed with differentiated thyroid cancer between January 2000 and December 2013 in the North Carolina Central Cancer Registry (CCR). CCR records were linked to state birth certificate files to identify livebirths to thyroid cancer survivors through December 2014. Person-years of follow-up were accrued from 6 months after diagnosis to first birth, 46(th) birthday, death, or December 31, 2014, whichever came first. Cox proportional hazards regression was used to estimate hazards ratios (HR) and 95% confidence intervals (CI) for first livebirth. Among 2,360 women with a differentiated thyroid cancer diagnosis, 53% received RAI. The cumulative incidence of birth at the end of follow-up (maximum 14.5 years) was 30.0% and 29.3% among those who were and were not treated with RAI, respectively. Overall, first birth rates did not significantly differ between groups (HR=1.00; 95% CI: 0.82, 1.23). In our observational cohort, treatment with RAI was not associated with a reduced birth rate. Our findings add to the evidence available for counseling thyroid cancer patients with concerns about future fertility.